PENGARUH PERSEPSI DUKUNGAN ORGANISASI DAN KEPRIBADIAN TERHADAP KEPUASAN KERJA GURU SD ISLAM AL AZHAR DI JAKARTA TIMUR - Nasjudi Nasjudi (Universitas Negeri Jakarta, 2015)
The purpose of this research is to determine the effect of perceived organization support and personality on job satisfaction the teacher state primary school al azhar, East Jakarta. The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) perceived organization support has a positive direct effect in job satisfaction, (2) personality has a positive direct effect in job satisfaction, (3) perceived organization support has a positive direct effect in personality.